Covid-19 Is Not A Barrier To Learning: A Lesson Learned From Islamic Boarding School - Iffat Maimunah; Arina Haque (FOUNDAE (Foundation of Advanced Education), 2021)
Â Mentoring and tutoring are fundamental needs for students, which should be able to run on an ongoing basis. Especially during the Covid-19 pandemic, mentoring and tutoring as a solution to strengthen understanding of school concepts and subjects for students in Islamic boarding schools. When students feel that there are difficulties in understanding school lessons due to the less than optimal online learning process and limited access to electronic media, mentoring, and tutoring are solutions that are able to bridge students in mastering school lessons, completing assignments, and question exercises. This service took place based on the results of observations and interviews related to the needs and anxieties of students regarding the learning process during the COVID-19 pandemic. Mentoring and tutoring are carried out using interactive discussion methods with students, as well as understanding the concept of subjects by completing non-religious subject matter exercises. Based on the results of the research obtained, mentoring and tutoring for students can help the students' learning process and their understanding of school lessons become better, as well as mentoring and study guidance being able to build motivation and enthusiasm for student learning to be better. Mentoring and tutoring are also able to formulate learning models to be more fun and happy because they can develop the concept of